It’s mathematics all the way down: revealing mathematical activity in non-formal learning spaces - Williams-Pierce, Caro; Katırcı, Nihal; Simpson, Amber; Shokeen, Ekta; Bih, Janet (Frontiers in Education, 2024)
We offer this synthesized framework as a tool to reveal mathematical activity in a non-formal making-space. In particular, we connect research at different grain sizes to illustrate and explain how mathematics plays a crucial, if often implicit, role in making activities. We begin by describing the Approximate Number System and the Ratio-Processing System, and explaining how those systems connect to both embodied cognition and Thompson's (1994) conceptualization of quantities. Then, we examine how prediction and anticipation relate, with a particular emphasis on how social feedback guided the emergent mathematical activity. We offer this framework as a way to perceive, account for, and understand the multi-layered nature of experiencing mathematical activities.